2002
DOI: 10.1002/jca.10040
|View full text |Cite
|
Sign up to set email alerts
|

Fuji surge technique and continuous in‐line filtration to improve the quality of single donor platelet concentrates

Abstract: White blood cell (WBC)-reduced single donor platelet concentrates (SDPs) can be collected by most cell separators. WBC reduction can be achieved directly during plateletpheresis or by filtration. Continuous filtration with low filtration rates provides SDPs of good purity. To compensate the platelet (PLT) loss due to filtration, the PLT yield in the unfiltered primary product should be optimal. Fifty donors underwent plateletpheresis with the MCS+ blood cell separator (Haemonetics) with the new Fuji surge tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The study showed that 80·51% (95 in 118) of the products after modification was qualified (Table ). Previous study demonstrated that MCS+ was the highest capacity for leukodepletion compared with other two devices of Amicus and Accel (Bueno et al , ) because of a continuous‐filtration technique for leukodepletion (Seghatchian & Krailadsiri, ; Seghatchian et al , ; Moog, ). The modification on the MCS+ resulted in less than 1 × 10 8 L −1 leukocyte in the selected samples, which complied with the international standard requirements (MnU‐B, ).…”
Section: Discussionmentioning
confidence: 97%
“…The study showed that 80·51% (95 in 118) of the products after modification was qualified (Table ). Previous study demonstrated that MCS+ was the highest capacity for leukodepletion compared with other two devices of Amicus and Accel (Bueno et al , ) because of a continuous‐filtration technique for leukodepletion (Seghatchian & Krailadsiri, ; Seghatchian et al , ; Moog, ). The modification on the MCS+ resulted in less than 1 × 10 8 L −1 leukocyte in the selected samples, which complied with the international standard requirements (MnU‐B, ).…”
Section: Discussionmentioning
confidence: 97%
“…Some of the common features shared by these systems are the possibility of obtaining a SDP (3.5 × 10 11 platelets [PLTs] per unit in our center), with an integrated leukodepletion system, as well as a plasma unit. For leukodepletion, the MCS Plus uses a continuous‐filtration technique 3,4 . Accel uses fluidized particle‐bed technology, 5‐7 whereas Amicus uses the elutriation principle 5,8‐12 .…”
Section: Methodsmentioning
confidence: 99%
“…One differential feature is that the Amicus uses saline for set priming at the beginning of the procedure, whereas the MCS Plus and the Accel use acid citrate dextrose‐A (ACD‐A). Various publications 4,9 , 10,13 have explained the function of these systems in great detail. The manufacturing companies configured the machines at their discretion to obtain the best possible results according to the objectives of the study.…”
Section: Methodsmentioning
confidence: 99%
“…All cytapheresis systems are capable to produce up to three white cell poor platelet units either in the apheresis procedure [9–12,14,15,25–34] or through an additional filtration step [27,29–31]. Multicomponent apheresis procedures using these techniques enable the concurrent collection of up to three platelet units alone or in combination with fresh frozen plasma fulfilling all quality criteria without the need of further manipulations [21,35–39].…”
Section: Multicomponent Collection Techniquesmentioning
confidence: 99%